Exhaled nitric oxide in mylar balloons: influence of storage time, humidity and temperature - Alessandro Bodini; Mariëlle W. H. Pijnenburg; Atillio L. Boner; Johan C. de Jongste (Mediators of Inflammation)
Background: Mylar balloons are used to collect exhaled air for analysis of fractional nitric oxide concentration (FENO).